Impact of Muscle Relaxation on Blood Pressure in Primary Hypertension Patients Sudiang Raya Makassar 2024 - Herdiansyah, Muh.; Arifin, Arina Fathiyyah; Muchsin, Achmad Harun; Wahyu, Sri; Arfah, Arni Isnaini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hypertension is a serious disease that causes serious complications such as stroke, local myocardial necrosis, cardiovascular disorders, and kidney failure. Hypertension is often nicknamed the